Factors influencing the exercise of supervisory powers of the accounting chamber of Ukraine - Коляда, Ю. О. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
The article attempts to investigate the constitutional obligation on the budget control by the supreme body of financial control in Ukraine. The author draws attention to the legal, economic and political factors that influence the activity of the Accounting Chamber of Ukraine at its current stage of the development. The research is based on the analysis of legislative acts of Ukraine and the standardized activity of the International Organization of Supreme Audit Institutions. The study revealed a lack of legal regulations that would allow the Accounting Chamber to develop and plan the budget in its establishment phase. Also, the attention is drawn to the functioning of the Accounting Chamber as a member of the international organization INTOSAI, and to a political factor through which the forms and methods of control of the supreme state body are improved. The compliance of the functions and performance of the Accounting Chamber with the documents of the international organization is determined. The article proposes to extend the authority of the Accounting Chamber not only as a legislative body, but also as a judiciary one, which will effectively influence the results of the audit. The author argues that the description of shortcomings by political, legal and economic factors allows solving the problems of the Accounting Chamber at different levels of government and with different approaches to improving constitutional duties on budget control. This particular way of presenting the material will facilitate a better understanding of the activities of the supreme bodies of financial control and their inapplicability to today’s new realities which are subject to various changes in the budgetary process. Foreign and domestic experience of using international standards that would allow revealing the shortcomings of the national formation of the state apparatus of supreme audit institutions in a comparative perspective is analyzed. The Federal Accounting Chamber of Germany has been chosen as an example of a supreme audit institution with the most advanced status and functions enshrined in the law, and effective in practice. The chamber has a status that allows it to be an instrument for budgeting between the legislative and executive branches of the government.